How has Gumbrecht read Heidegger? The notion of presence as forgetting the Forgetfulnes of being - Carneiro, Gabriel Barroso Vertulli (2025)
The objective of this article is to question a specific point of Hans Ulrich Gumbrecht’s reading of Martin Heidegger. The aim is to problematize Gumbrecht’s statement that there would be a convergence between his notion of “presence” and Heidegger’s concept of “being”. From an examination of Heidegger’s interpretation of the term ousia, we aim to demonstrate that being and presence could not converge insofar as making the being present would be ignoring the ontological difference – that is, the difference between being and beings. If Gumbrecht’s intention was in fact to present being, he ends up making it substantializable and, consequently, his notion of presence would operate based on a “forgetting of the forgetting of being”.